LMX as mediator of organizational justice and employee work engagement relationship: evidence from the Middle East - Hassan, Arif; Al Jubari, Ibrahim Hizam Ali (2010)
The paper examines the role that organizational justice plays in determining employees’ work engagement and the way quality of leader-subordinate relationship (LMX) mediates this association. Data was obtained from an airline company from the middle-east. Sample consisted of 218 employees from several job levels who responded to a questionnaire measuring the study variables. Results indicated that distributive and procedural justice perception promoted quality relationship between leader and subordinate and higher quality of leader-subordinate relationship contributed to employees’ work engagement. Among the three organizational justice factors, only interactional justice was related to employee work engagement. The study found a full mediation effect of LMX on interactional justice and employee work engagement relationship.